PENGARUH PEOPLE, PROSES DAN ATMOSPHERE TOKO TERHADAP KEPUTUSAN PEMBELIAN DI TOKO PUTRA KEMBAR 2 - Muhammad Machyar Barlian; Wina Almayanti; Ajat Sudrajat (Ekonomi & Bisnis, 2022)
This study aims to determine the effect of people, processes, and store atmosphere either partially or simultaneously on consumer purchasing decisions at Toko Putra Kembar 2. This research is a survey research using a questionnaire as an instrument. The population used in this study were local residents who had made a purchase at the Putra Kembar 2 Store, Dusun Krajan RT 009 RW 001 Desa Pasir Kamuning, Kec. Telagasari, Karawang Regency, West Java. ID 41381. The sample was taken as many as 100 respondents using the Uses and Gratifications Theory method and using a type of regression analysis research, where this study will examine the relationship whether there is an influence between one independent variable on another variable. To test the validity is to use the Bivariate Pearson correlation. While the reliability test uses Cronbach's Alpha. The analysis technique used is multiple regression analysis. The results of the study found that the people variable (X1) had a positive effect on purchasing decisions (Y). The calculated T value was 2.771 > T table 1.962 with a sig value of 0.007 <0.05. So it can be concluded that the process variable (X2) has a positive effect on purchasing decisions (Y). The calculated T value is 5.562 > T table is 1.962 with a sig value of 0.000 <0.05. So it can be concluded that the atmosphere variable (X3) has a positive effect on purchasing decisions (Y). Keywords: People, Process, Atmosphere Store, consumer purchasing decisions.